2010
DOI: 10.1056/nejmoa0808939
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Surgical-Site Infections in Nasal Carriers ofStaphylococcus aureus

Abstract: The number of surgical-site S. aureus infections acquired in the hospital can be reduced by rapid screening and decolonizing of nasal carriers of S. aureus on admission. (Current Controlled Trials number, ISRCTN56186788.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
568
0
17

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,075 publications
(602 citation statements)
references
References 28 publications
17
568
0
17
Order By: Relevance
“…2A) [9,11,16,20,24,26,30,43,47], the reduction of S. aureus SSIs ranged from 40% to 200% (Fig. 2B) [5,9,16,19,42,51], the reduction of MRSA SSIs ranged from 29% to 149% (Fig. 2C) [9,29,36,40,49,57], and the reduction of wound complications was reported at 4% in one study [7].…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…2A) [9,11,16,20,24,26,30,43,47], the reduction of S. aureus SSIs ranged from 40% to 200% (Fig. 2B) [5,9,16,19,42,51], the reduction of MRSA SSIs ranged from 29% to 149% (Fig. 2C) [9,29,36,40,49,57], and the reduction of wound complications was reported at 4% in one study [7].…”
Section: Resultsmentioning
confidence: 92%
“…When evaluating the location of different SSIs, four studies showed that there was no statistically significant difference between the intervention group and the nonintervention group regarding deep or superficial SSIs [26,42,43,49]. However, one study [5] that decolonized only screen positive patients showed that the rate of deep SSIs decreased with use of a S. aureus decolonization protocol, and another study [29] that also decolonized only screen positive patients showed there was a significant decrease in deep SSIs with decolonization and moderate decrease in organ space or joint SSIs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations